Efek Moderasi Sistem Pengendalian Internal Pemerintah; Pengaruh Peran Pengawasan APIP Terhadap Kualitas Penyajian Laporan Keuangan - Pesireron, Semy; Tuhumena, Aleida Marryane (ISAS, 2025)
The objective of this study is to empirically investigate the effect of the role of the government’s internal supervisory apparatus on the quality of financial statement presentation, as well as to examine the moderating influence of the government’s internal control system on this relationship within the West Southwest Maluku Regency Government. Data were collected through a survey method by distributing questionnaires to selected respondents, using a purposive sampling technique. The data were analyzed employing moderated regression analysis with a significance level of 0.05. The findings indicate that the supervisory role of the internal government auditors exerts a significant influence on the quality of financial statement presentation in the West Southwest Maluku Regency Government. Moreover, the government’s internal control system is found to moderate the relationship between the supervisory role of the internal government auditors and the quality of financial statement presentation, thereby strengthening the effect within the governmental context of West Southwest Maluku Regency. Keywords: Government Internal Supervisory Apparatus; Government Internal Control System; Quality of Financial Statement Presentation